Wet purpura in Dengue fever - Manappallil, Robin George; Yelisetti, Mounika (Asian Journal of Medical Sciences, 2018)
Dengue fever is an acute febrile viral illness associated with severe headache, myalgia, arthralgia, rashes, leucopenia and thrombocytopenia. These patients can present with haemorrhagic manifestations. Wet purpura in oral mucosa occurs when there is a drastic fall in platelet counts; and can be taken as a sign of impending systemic haemorrhage. This is the case of a young male who was diagnosed to have Dengue fever. He developed severe thrombocytopenia and wet purpura, following which he had gastrointestinal bleed. Dengue fever presenting with wet purpura is a rare scenario. Asian Journal of Medical Sciences Vol.9(2) 2018 43-44